Knee Arthrodesis in Persistently Infected Total Knee Arthroplasty - Balci, Halil Ibrahim; Saglam, Yavuz; Pehlivanoglu, Tuna; Sen, Cengiz; Eralp, Levent; Kocaoglu, Mehmet (The Journal of Knee Surgery, 2016)
The reported incidence of infection in total knee arthroplasty (TKA) varies from 0.5 to 15%. The most common indication for knee arthrodesis is persistent infection after repeated staged knee replacement. The purpose of this study is to investigate the success of fusion with monoplanar fixators and eradication rates of infection, and to evaluate the satisfaction of patients who underwent a last-resort TKA due to infection.This is a retrospective review of infected knee arthroplasties that were treated with knee arthrodesis using unilateral external fixators at a single institution from 1999 through 2012. The patients' charts were analyzed for demographics, types of external fixators used, infection parameters, external fixator indexes, complications, positions of fusion, and leg length discrepancies (LLDs). Patients were called back to return for additional follow-up. A self-administered general health status questionnaire (SF-36) was assessed to evaluate life quality.There were 14 women and 3 men with an average age of 67 ± 16.6 years. Antibiotic-loaded acrylic cements were used as a spacer for an average of 3.4 ± 1.2 months in all patients. Monoplanar type of external fixator was used in all 17 patients. Fusions were achieved in all but one patient. The mean duration of fusion was 6.8 ± 2.2 months and external fixator duration was 7.6 ± 2.4 months. Average LLD was 2.9 ± 1.7 cm. The mean coronal alignment of fusion was 6.8 degrees (± 3.3 degrees, range 4–15 degrees) valgus and mean flexion was 11.3 degrees (± 6.5 degrees, range 3–30 degrees). Compared with the healthy controls, the SF-36 scores were significantly lower in patients with knee arthrodesis (physical component score [PCS]-arthrodesis: 39.3 vs. PCS- healthy controls: 47.9, p < 0.05; mental component score [MCS]-arthrodesis: 38.6 versus MCS-healthy controls: 47.7, p < 0.05).Use of monoplanar fixators for arthrodesis in infected TKA can achieve high fusion rates with the control of infection. If fusion can be achieved, the patient satisfaction is low with acceptable pain relief and functionality. We observed that monoplanar external fixators increased patients' comfort levels compared with circular external fixators. Further studies are needed to compare different arthrodesis modalities in patients with infected TKA.
Keywords: knee arthrodesis; total knee arthroplasty; periprosthetic infection; SF-36